Akseptabilitas Konsep Integrasi Pendidikan Islam dalam Sistem Pendidikan Nasional - Akhiyat, Akhiyat (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
The dichotomy of the education system causes a gap between the sourcesof knowledge, between the religious sciences and general sciences. In thebook Integrasi Ilmu: Sebuah Rekonstruksi Holistik, the supporters of thereligious sciences only consider divine source and prophetic tradition asvalid sources and reject the others. On the other hand, secular scientistsonly considered valid information obtained through sensory observation.Therefore, the integration of Islamic education in the national educationsystem is part of the problems. According to the writer, the approachshould be integrated. All legislation and policies made by the government(which appears to lead to the integration) are effort to prepare and realizethe law of “one national education system